(3eQGM GdCQhGMs - (3CHh GdaVGFd, MSGe GdOjf, CMeO Hf Ydj Hf eSYhO, J (B700(3g`s
(3ChdgG (B:s
(3OGQhgG hjWaj aj GdQhGjGJ YGQhgG, aLeYJ ajg cJGHG ehSheG H`(B... (3gh ddUHj LfGM(B... (3GdUQa jMJGL aj eYQaI GdChRGf Edi SHYI CHhGH(B...s
(3BNQgG (B:s
(3hGddJj de JLeY GdEYdGdGf jchf McegG CjVG cMc Whi ddeHGdZI fMh WhjG hWGhjGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B175s
(3cTa GdXfhf(B: (3L(B2(3, U(B1651s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas